The Invasive Caucasian Populations of the Brown Marmorated Stink Bug Halyomorpha halys (Hemiptera: Heteroptera: Pentatomidae) Rapidly Adapt Their Ecophysiological Traits to the Local Environmental Conditions - Sergey Ya. Reznik; Margarita Yu. Dolgovskaya; Natalia N. Karpun; Vilena Ye. Zakharchenko; Aida Kh. Saulich; Dmitrii L. Musolin (Insects, 2023)
The ability to rapidly adapt to new environmental conditions is a crucial prerequisite for the wide-scale invasion of pests or intentional introduction of beneficial insects. A photoperiodically induced facultative winter diapause is an important adaptation ensuring synchronization of insect development and reproduction with the local seasonal dynamics of environmental factors. We conducted a laboratory study aimed to compare photoperiodic responses of two invasive Caucasian populations of the brown marmorated stink bug Halyomorpha halys (Hemiptera: Heteroptera: Pentatomidae), which recently invaded neighboring regions with subtropical (Sukhum, Abkhazia) and temperate (Abinsk, Russia) climates. Under the temperature of 25 °C and the near-critical photoperiods of L:D = 15:9 h and 15.5:8.5 h, the population from Abinsk showed a slower pre-adult development and a stronger tendency to enter winter adult (reproductive) diapause compared to the population from Sukhum. This finding agreed with the difference between the local dynamics of the autumnal temperature decrease. Similar adaptive interpopulation differences in the patterns of diapause-inducing responses are known in other insect species but our finding is distinguished by a very short adaptation time: H. halys was first recorded in Sukhum in 2015 and in Abinsk in 2018. Thus, the differences between the compared populations might have evolved over a relatively short span of several years.